2019
DOI: 10.1111/jdv.15964
|View full text |Cite
|
Sign up to set email alerts
|

The association between pesticide use and cutaneous melanoma: a systematic review and meta‐analysis

Abstract: Background The incidence of cutaneous melanoma (CM), the deadliest form of skin cancer, has gradually increased in the last decades among populations of European origin. Epidemiological studies suggested that farmers and agricultural workers are at an increased risk of CM because they were exposed to pesticides. However, little is known about the relationship between pesticides and CM. Objectives To investigate the association between exposure to pesticides and CM by systematically reviewing the literature. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“… 22 In contrast, recently conducted meta‐analyses do not support the relationship between CMM and exposure to PCBs and OCs. 7 , 8 , 23 While the studies included in the meta‐analyses were mostly from occupational settings with presumably much higher exposure levels, few of the studies involved direct assessment of POP body burdens. Variability in mixtures of PCBs and OCs to which populations are exposed, 6 as well as heterogeneous study designs (case–control vs. cohort) as well as variability in adjustment for potential confounders (e.g., UV/sun exposure) could potentially explain the mixed associations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 22 In contrast, recently conducted meta‐analyses do not support the relationship between CMM and exposure to PCBs and OCs. 7 , 8 , 23 While the studies included in the meta‐analyses were mostly from occupational settings with presumably much higher exposure levels, few of the studies involved direct assessment of POP body burdens. Variability in mixtures of PCBs and OCs to which populations are exposed, 6 as well as heterogeneous study designs (case–control vs. cohort) as well as variability in adjustment for potential confounders (e.g., UV/sun exposure) could potentially explain the mixed associations.…”
Section: Discussionmentioning
confidence: 99%
“…5 While oxidative stress and chronic inflammation have been speculated as mechanisms by which pesticides may increase cancer risk, an actual mechanism has not been identified. 23 , 24 PCBs and OC pesticides may also induce carcinogenesis through epigenetic mechanisms. Multiple studies have reported significant associations between DNA methylation and exposure to PCBs and OC pesticides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review found an association between pesticide use and development of cutaneous malignant melanoma 17 …”
Section: Environmental Influencesmentioning
confidence: 99%
“…To reduce the exposure, the farmer used the wild plant called acem acem leaves or Oxalis dehradunensis Raizada as a medium to clean the soil impurities and pesticides. [ 1 2 3 4 5 6 7 8 ]…”
Section: Introductionmentioning
confidence: 99%